circFOXP1: a potential diagnostic and therapeutic target in human diseases - Yi, Qiang; Ouyang, Xinting; Zhong, Kui; Chen, Zheng; Zhu, Weijian; Zhu, Gangfeng (Frontiers in Immunology, 2024)
Circular RNA (circRNA) are a unique class of non-coding RNAs characterized by their covalently closed loop structures, which grant them properties such as stability and conservation. Among these, circFOXP1 has been implicated in various diseases, including cancers, respiratory, skeletal, and cardiovascular disorders. This review systematically examines circFOXP1’s role in disease progression, highlighting its involvement in critical biological processes, including cell proliferation, invasion, apoptosis, and autophagy. Mechanistically, circFOXP1 functions through miRNA sponging, protein interactions, and modulation of key signaling pathways such as Wnt and PI3K/AKT. We discuss its potential as a diagnostic and therapeutic target. Our analysis also identifies key unresolved questions, such as the precise regulatory networks involving circFOXP1 and its translation potential, offering pathways for future research.